Gas Sensing Properties of Pure and Co Surface Modified Nanocrystalline SmFeO3 Thick Films - Mankar, Rajendra B.; Kapse, Vivek D.; Patil, D.R. (Asian Journal of Chemistry, 2023)
In present work, nanocrystalline SmFeO3 perovskite oxide powder was prepared by sol-gel method. Thick films of SmFeO3 were fabricated onto a glass substrate by screen printing technique and heated at 500 ºC for 30 min. As-prepared pure nanocrystalline SmFeO3 thick films were dipped into 0.1 M aqueous solution of cobalt chloride for different intervals of time. Microstructure and surface morphology of both pure and Co surface modified SmFeO3 thick films were investigated by energy dispersive X-ray analysis (EDAX) and field effect scanning electron microscopy (FE-SEM) techniques. The FE-SEM micrograph reveals the porous nature of thick films. EDAX analysis showed that both pure and Co modified thick films are oxygen deficient. Gas sensing performance of these films was tested for different gases. The highest response and selectivity was recorded to 50 ppm NH3 gas at 200 ºC for SmFeO3 thick film dipped into cobalt chloride solution for 3 min. The effect of cobalt doping and its dipping time on microstructure, surface morphology and gas sensing properties of pure SmFeO3 thick film was discussed.